ЗЕРЕНДІ КӨЛІНЕН АЛЫНҒАН СУ ҮЛГІЛЕРІНЕ CHLORELLA SP-3K ШТАМЫН ӨСІРУ АРҚЫЛЫ БИОТЕСТ ЖҮРГІЗГЕН НƏТИЖЕЛЕР (Experimental biology, 2017)
Respective was biotesting lakes on cultures of microseaweed allocated with water ecosystem of lakes Кокshetau region is carried out is especial on strain Chlorella sp-3K, distinguished fast duplicate and clearing ability of pollution of natural waters. As a result of biotesting, is revealed, that waters of lake Zerenda an average level toxicity: growth of crates average 16,8±0,5 mln/ml.
Keywords: Chlorella sp-3K